2010
DOI: 10.1016/j.jacc.2010.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cytochrome P450 2C19 Loss-of-Function Polymorphism and of Major Demographic Characteristics on Residual Platelet Function After Loading and Maintenance Treatment With Clopidogrel in Patients Undergoing Elective Coronary Stent Placement

Abstract: Thus, our study does not suggest that, in patients critically dependent on adequate platelet inhibition, genotyping alone or in combination with clinical factors can replace phenotyping of platelet function. (Effect of Clopidogrel Loading and Risk of PCI [EXCELSIOR]; NCT00457236).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
199
3
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(224 citation statements)
references
References 35 publications
(49 reference statements)
15
199
3
7
Order By: Relevance
“…In clopidogrel users, diabetes and hypercholesterolaemia were associated with a higher risk of antiplatelet drug nonpersistence. Although this was unexpected, it might be partly explained by the concern of a pharmacokinetic interaction between atorvastatin and clopidogrel in patients with hypercholesterolaemia 26, and diabetes was reported as a predictor of insufficient antiplatelet response to clopidogrel 27. Patients with previous CAD, who also have a higher risk for recurrent cardiovascular events, had a lower risk of clopidogrel nonpersistence but a higher risk of DAPT nonpersistence.…”
Section: Discussionmentioning
confidence: 95%
“…In clopidogrel users, diabetes and hypercholesterolaemia were associated with a higher risk of antiplatelet drug nonpersistence. Although this was unexpected, it might be partly explained by the concern of a pharmacokinetic interaction between atorvastatin and clopidogrel in patients with hypercholesterolaemia 26, and diabetes was reported as a predictor of insufficient antiplatelet response to clopidogrel 27. Patients with previous CAD, who also have a higher risk for recurrent cardiovascular events, had a lower risk of clopidogrel nonpersistence but a higher risk of DAPT nonpersistence.…”
Section: Discussionmentioning
confidence: 95%
“…The presence of a gene polymorphism resulting in loss of function of the drug-metabolizing enzyme CYP2C19 was found to be an important factor. 23,24 A recent study from the Thrombolysis in Myocardial Infarction (TIMI) study group confirmed that heterozygote and homozygote carriers of the allele retain high platelet function on clopidogrel treatment. 25 This study demonstrated that increasing daily doses of clopidogrel can produce levels similar to those in noncarriers in heterozygotes.…”
Section: Discussionmentioning
confidence: 98%
“…In a combined model, age, body mass index and presence or absence of diabetes accounted for 1% each of platelet aggregation variability. CYP2C19*2 carrier status alone accounted for 5.2% of platelet aggregation variability and CYP2C19*2 plus clinical variables was accounted for 11.5% of platelet aggregation [36]. In the POPULAR study, CYP2C19*2 genotype was associated with approximately 4-6% and clinical variables with 9-17% variability in on-treatment platelet reactivity as assessed by ADP-induced platelet aggregation and VerifyNow P2Y12 assay.…”
Section: Influence Of Cyp2c19 Polymorphisms On Clopidogrel Metabolismmentioning
confidence: 93%